De certaines dispositions de la loi sur les sociétés commerciales canadiennes - Camirand, Marcel (Assurances, 1981)
This is the second part of Mr. Marcel Camirand's paper on the latest conception of the Commercial Corporation, the solvability test and the personal liability of directors under certain conditions and for certain operations of the Corporation, considered under the angle of the federal law.